ECM and epithelial stem cells: the scaffold of destiny - Estrach, Soline; Vivier, Charles-Maxime; Féral, Chloé C. (Frontiers in Cell and Developmental Biology, 2024)
Adult stem cells play a critical role in maintaining tissue homeostasis and promoting longevity. The intricate organization and presence of common markers among adult epithelial stem cells in the intestine, lung, and skin serve as hallmarks of these cells. The specific location pattern of these cells within their respective organs highlights the significance of the niche in which they reside.The extracellular matrix (ECM) not only provides physical support but also acts as a reservoir for various biochemical and biophysical signals. We will consider differences in proliferation, repair, and regenerative capacities of the three epithelia and review how environmental cues emerging from the niche regulate cell fate. These cues are transduced via mechanosignaling, regulating gene expression, and bring us to the concept of the fate scaffold.Understanding both the analogies and discrepancies in the mechanisms that govern stem cell fate in various organs can offer valuable insights for rejuvenation therapy and tissue engineering.